Using Authentic Materials in Foreign Language Classrooms: Teachers' Perspectives in the Department of English, Faculty of Arts at El-Mergib University - Khiri Saad Elkut; Khairi Alarbi Zaglom; Foad Ashur Elbakay; Ahmad Mohamed Omeman (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
The use of authentic materials in EFL classrooms has been a dominant and influential practice for many decades. Many teachers incorporate authentic materials in their classes due to the numerous benefits they offer to students but some teachers may not. Hence, this study investigates whether teachers of English in the Department of English in Faculty of Arts at El-Mergib University use authentic materials in their classes or not, and if they face any difficulties in doing so. To achieve this goal, a questionnaire was administered to ten teachers of English. The findings of the study revealed that teachers of English have positive perspectives towards integrating authentic materials into their language teaching.